ANALISIS PENGENDALIAN KUALITAS PRODUKSI PADA PERUSAHAAN MEUBEL UD. BAROKAH INDAH DI KOTA KUPANG - Noe, Karolus Boromeus; Nyoko, Antonio E L; Fanggidae, Ronald P C (GLORY Jurnal Ekonomi dan Ilmu Sosial, 2022)
This research was conducted at the UD Furniture company. Beautiful Barokah in the city of Kupang. The purpose of this study was to analyze the production quality control of UD furniture. Beautiful Barokah in Kupang City. There are two sources of data in this study, namely primary data and secondary data. Primary data is data obtained by the author directly through interviews or company leaders at UD. Barokah Indah and secondary data are data obtained from literature documentation and books related to research. The data analysis technique used is eight steps of improvement which are the result of the method of solving problems or increasing success based on a continuous plan do check action (PDCA) cycle. The results of this study were obtained from quality control activities carried out by the UD Furniture company. Barokah Indah, namely: (a) quality control of raw materials, (b) control of the production process, (c) control of finished products. The conclusion that can be drawn from the results of the analysis conducted by researchers at the UD furniture company. Barokah Indah said that there were two factors that caused the damage, namely the half-defect factor and the pest attack factor. Keywords: Type Of Damage, Furniture, Quality Control, Level Of Damage